2010
DOI: 10.18433/j30k5q
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Protects Against Methotrexate-Induced Hepatic Injury in Rats

Abstract: -Purpose. The aim of this study was to investigate the possible protective effect of resveratrol on some liver and blood parameters in methotrexate (MTX) induced toxicity in rats. MTX is used widely to treat various neoplastic diseases such as acute lymphoblastic leukemia, lymphoma, solid cancers, and autoimmune diseases. We hypothesized that resveratrol has a potential to decrease the oxidant damage in MTX-induced hepatic injury. Methods. Following a single dose of methotrexate (20 mg/kg, i.p.), either saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
47
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 36 publications
11
47
0
2
Order By: Relevance
“…Thus, manipulation of Bcl-2 family proteins through resveratrol might contribute to the life or death decision for cells under oxidative stress. Interestingly, in contrast to experiments from cancer cell lines, resveratrol was able to protect hepatic tissue [39][40][41]. Consistent with these in vivo studies, we found that resveratrol treatment decreased hepatic cellular apoptotsis in the BDL model.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, manipulation of Bcl-2 family proteins through resveratrol might contribute to the life or death decision for cells under oxidative stress. Interestingly, in contrast to experiments from cancer cell lines, resveratrol was able to protect hepatic tissue [39][40][41]. Consistent with these in vivo studies, we found that resveratrol treatment decreased hepatic cellular apoptotsis in the BDL model.…”
Section: Discussionsupporting
confidence: 87%
“…Lyc, a powerful anti-oxidant, has been showed to be effective in reducing the nephrotoxicity caused by cisplatin, via decreasing oxidative stress (4,(38)(39)(40). Lyc's also has anti-infl ammatory and anti-cancer properties.The studies showed that it may be effective in reducing organ toxicity such as pancreas, testis and kidney (39,(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, many studies have shown that high-dose MTX treatment can induce increased oxidative stress, resulting in renal and liver damage (3,3537). However, the specific reactive oxygen species (ROS) induced by MTX treatment have not been identified.…”
Section: Introductionmentioning
confidence: 99%